Association of lymphoid tissue‐resident commensal bacteria in mice with depressive‐like behaviors induced by chronic social defeat stress. Issue 6 (25th April 2020) - Xie, Ruining; Jiang, Pei; Lin, Li; Yu, Bin; Wang, Chunmei; Pan, Yanyou; Rao, Jingjing; Wei, Wei; Qiao, Yi
Abstract: Emerging evidence suggests that the microbiota‐gut‐brain axis affects a variety of complex behaviors, including social, emotional, and depressive‐like behaviors. Peyer's patches (PPs), a well‐characterized gut‐associated lymphoid tissue, are the entry site for luminal antigens and the initiation site for antigen‐specific immune responses. However, few studies have explored the composition of lymphoid tissue‐resident commensal bacteria (LRCs) in stress‐associated disorders. Male C57BL/6 mice exposed to chronic social stress were analyzed for microbiome on the interior of PPs and changes in inflammation. Susceptible mice (SUS) exhibited a composition of bacteria inside PPs that was distinct from that of control (CON) and resilient (RES) mice, including an increase in Candidatus Arthromitus (SFB) and a decrease in Lactobacillus. The CD4 + CD25 + Foxp3 + T cells were significantly reduced in SUS mice. Relative mRNA levels of IL‐2 were significantly reduced in SUS mice, and the mRNA levels of Bcl‐6, IFN‐γ, IL‐6, and the IgA protein levels in the ileum were significantly increased. Moreover, in the prefrontal cortex of SUS mice, IL‐6 and TNF‐α were increased, whereas IL‐10 was decreased. The correlational analyses revealed that social interaction ratio was negatively correlated with SFB and positively associated with Lactobacillus and four other candidate protective organisms. These results pointed the possibility that the changes in the LRCs induced by chronic social defeat stress were ultimately associated with the inflammation of the brain and exacerbation of depressive‐like behaviors.